Is the Virtual Integration of Financial Markets Beneficial in Emerging Markets? Evidence from Mila - Espinosa-Mendez, C; Gorigoitia-Gallardo, J (Routledge, 2017)
This article analyzes whether the Latin American Integrated Market (MILA) has been beneficial for its participants. Using a dynamic conditional correlation (DCC) model proposed by Engle (2002), we found evidence that creating MILA increased the correlation levels in stock returns of member countries. Evidence indicates that this increase occurs mainly due to the increase in traded volume in the country with the least developed stock market—Peru. In short, findings suggest that in an integration process such as MILA, as stock market members differ, in terms of stock market development, the markets will benefit from the integration. However, in the long term these benefits dissipate over time. Copyright © Taylor & Francis Group, LLC.